2016
DOI: 10.1186/s40673-016-0051-5
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar involvement in Parkinson’s disease resting tremor

Abstract: BackgroundThere exists a lack of consensus regarding how cerebellar over-activity might influence tremor in Parkinson’s disease (PD). Specifically, it is unclear whether resting or postural tremor are differentially affected by cerebellar dysfunction. It is important to note that previous studies have only evaluated the influence of inhibitory stimulation on the lateral cerebellum, and have not considered the medial cerebellum. The aim of the current study was to compare the effects of a low-frequency rTMS pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…An important aspect that one has to bear in mind when interpreting patterns of activity in M1 is the fact that M1 is the target of somatotopically organized outputs from both the basal ganglia and cerebellum . Although it is not clearly understood how the basal ganglia and cerebellum interact with each other, there is increasing evidence on the involvement of the cerebellum in resting tremor in PD, and it could be that information processing along this parallel pathway connecting the cerebellum to cortical motor areas contributes to and modulates the pathophysiological state of M1 in PD. Finally, although the existing dichotomy of functional activity in M1 as revealed by nuclear imaging and MRI may seem somewhat contradictory, it also raises the question whether PD may be associated with a patterned combination of hypo‐ and hyperactivity.…”
Section: Imaging the Parkinsonian Brain: What Have We Learned About Tmentioning
confidence: 99%
“…An important aspect that one has to bear in mind when interpreting patterns of activity in M1 is the fact that M1 is the target of somatotopically organized outputs from both the basal ganglia and cerebellum . Although it is not clearly understood how the basal ganglia and cerebellum interact with each other, there is increasing evidence on the involvement of the cerebellum in resting tremor in PD, and it could be that information processing along this parallel pathway connecting the cerebellum to cortical motor areas contributes to and modulates the pathophysiological state of M1 in PD. Finally, although the existing dichotomy of functional activity in M1 as revealed by nuclear imaging and MRI may seem somewhat contradictory, it also raises the question whether PD may be associated with a patterned combination of hypo‐ and hyperactivity.…”
Section: Imaging the Parkinsonian Brain: What Have We Learned About Tmentioning
confidence: 99%
“…The study authors concluded that the CTC pathway was not primarily driving the rest tremor. However, in another study by Lefaivre et al, rest tremor as rated by kinematic parameters was reduced by lowfrequency rTMS targeted to the medial and lateral cerebellum (43). These two studies used different stimulation techniques and there were differences in clinical populations, which could explain the conflicting results.…”
Section: Therapeutic Use Of Rtmsmentioning
confidence: 97%
“…This may have been due to additional thalamic and cerebellar dysfunctions in these patients that could act as compensatory mechanisms which curb the effects of nigrostriatal depletion, thereby masking parkinsonism features 42 . Indeed, both thalamic and cerebellar inhibition has been shown to improve features such as tremor in PD patients 75,76 . These, and perhaps other compensatory mechanisms, may become ineffective at a more advanced stage of disease and ultimately result in a parkinsonism phenotype in some cases.…”
Section: Mtdna Maintenance Genes As Pd Risk Factorsmentioning
confidence: 99%